Exploring Green Consumption Trends and Consumer Behavior toward Hydroponic Vegetables in Post-Pandemic China - Jiang Wenlu; Lu Ruixin; Zhang Zheyu (SHS Web of Conferences)
Against the backdrop of global climate change and China's dual-carbon strategy, hydroponic vegetables have emerged as a promising solution for sustainable agriculture and healthy diets. This study focuses on the intersection of agricultural transformation and green consumption behavior, aiming to reveal consumer awareness, psychological decision-making mechanisms, and influencing factors of hydroponic vegetable adoption. Based on a nationwide mixed-method survey covering 23 provinces, we analyzed differences across demographic groups using stratified sampling. The results show: (1) increasing public recognition of hydroponic technology and eco-friendly products; (2) a “tech perception–eco identity–cost barrier” triadic decision logic; and (3) significant generational and income-related differences in demand preferences. Additionally, green consumption behaviors are found to be rising, but behavioral paradoxes— such as attitude-behavior gaps due to price sensitivity—remain prominent. We propose differentiated marketing strategies and policy support tools, such as tax incentives and standard certifications, to enhance market penetration. This research contributes to the theory of green consumer behavior and provides valuable references for sustainable agri-food market development.